2020
DOI: 10.2147/ott.s268694
|View full text |Cite
|
Sign up to set email alerts
|

<p>Response to Afatinib in a Patient with NSCLC Harboring Novel <em>EGFR</em> Exon 20 Insertion Mutations</p>

Abstract: Most epidermal growth factor receptor (EGFR) exon 20 insertion (ex20ins) mutations are resistant to tyrosine kinase inhibitors (TKIs). While some non-small cell lung cancer (NSCLC) patients harboring special subtypes of EGFR ex20ins still achieved clinical response after TKIs treatment, identifying special subtypes of EGFR ex20ins is helpful to find out NSCLC patients who can respond to TKIs. Case Presentation: A 71-year-old non-smoker Chinese female was diagnosed with advanced lung adenocarcinoma harboring EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…[11][12][13] Nevertheless, several studies have shown durable responses to afatinib in patients who harbor exon-20ins mutations near codon 770. [14][15][16] Similarly, the efficacy of third-generation EGFR TKIs is also controversial.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Nevertheless, several studies have shown durable responses to afatinib in patients who harbor exon-20ins mutations near codon 770. [14][15][16] Similarly, the efficacy of third-generation EGFR TKIs is also controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the average IC50 values for afatinib and osimertinib across 6 EGFR ex20ins mutants (A767insASV, S768dupSVD, V769insASV, D770insNPG, D770insSVD, H773insNPH) were 39.9 nM and 103 nM, respectively ( 23 ). And afatinib achieved a durable response in a small number of NSCLC patients harboring specific EGFR ex20ins mutations ( 24 – 27 ). Similarly, poziotinib has a less rigid core and smaller terminal groups than osimertinib, which allows it to assess the restricted drug-binding pocket of EGFR ex20ins mutants more easily ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…22 Case reports have described sensitivity to afatinib of H773dup, H773_V774insNPH, and N771delinsKG mutations. [23][24][25] In-frame insertions of exon 20 occur also in HER2 in approximately 1-2% of NSCLC. Exon20ins mutations of HER2 are less heterogenous than those of EGFR, with Y772dupYVMA and A775_G776insYVMA accounting for more than 80% of the cases.…”
Section: The Context Of Exon20ins Inhibitorsmentioning
confidence: 99%